Pathways to excellence developing and cultivating leaders for the classroom and beyond - Lahera, Antonia Issa; Hamdan, Kamal; Normore, Anthony H. (Advances in educational administration ;, 2014)
Pathways to excellence : developing and cultivating leaders for the classroom and beyond examines how leadership and layers of leaders are developed and cultivated from the classroom to the boardroom. A wide body of research exists that focuses on specific educational leadership development and training programs. Evidence of being ready to lead upon program completion and performance post preparation is less available. Scant attention has been paid to programs that prepare leaders in different layers of an organization to not only become individually high performing but to also work collaboratively to create great schools. The book contends that the principal cannot effectively lead a school alone - other key players are critical. The editors have cast a wide net of respected contributors from various levels of organizational school leadership and specialties including traditional schools, charter schools, teacher education, district level leadership, special education, master teacher leadership, university and college level leadership. Implications for theory and practice will be discussed as it relates to leadership development and preparation of key players and constituents.